Scholars' physical appearance, research performance and feelings of happiness - Alexander Dilger; Laura Lütkenhöner; Harry Müller (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2013)
Our study aims to analyse whether former feelings of happiness and/or physical appearance have influence on the subsequent observable research performance of scholars. Therefore we photographed 49 persons attending the 72nd annual conference of the German Academic Association for Business Research (VHB), which took place in Bremen in 2010. We interviewed them about their feelings of happiness. Later we asked students to evaluate the photographed persons' attractiveness, competence, trustworthiness, likeability and their feelings of happiness. To determine the academics' research performance we compiled a list of their recent journal publications, considering different journal weights and dividing them by the number of authors. Regression analyses reveal that feelings of happiness in 2010 significantly increase research performance in 2011/2012. In addition, they suggest that scholars' physical appearance can affect their research performance. In particular we observe that a trustworthy appearance has a significantly positive effect. – – Wir untersuchen empirisch, ob vorheriges Glücksempfinden und/oder Aussehen die zu einem späteren Zeitpunkt beobachtbare Forschungsleistung von Wissenschaftlern beeinflussen. Im Jahr 2010 wurden 49 Teilnehmer der 72. Jahrestagung des Verbands der Hochschullehrer für Betriebswirtschaft (VHB) fotografiert und danach gefragt, wie glücklich sie sind. Anschließend wurden Studenten gebeten, anhand der Portraits die Attraktivität sowie die ausgestrahlte Kompetenz, die Vertrauenswürdigkeit, die Sympathie und das Glücksempfinden der fotografierten Personen zu bewerten. Deren Forschungsleistung wurde anhand ihrer Veröffentlichungen in Fachzeitschriften in den letzten Jahren quantifiziert, wobei unterschiedliche Gewichtungen von Zeitschriften berücksichtigt wurden und eine Division durch die Anzahl der Autoren stattfand. Regressionsanalysen ergeben, dass Glücksempfinden in 2010 die Forschungsleistung in 2011/2012 signifikant erhöht. Außerdem deuten sie darauf hin, dass sich das Aussehen von Wissenschaftlern auf ihre Forschungsleistung auswirkt. Insbesondere ist zu beobachten, dass ein vertrauenswürdiges Aussehen einen signifikant positiven Einfluss hat.
Keywords: I23; J01; M00; M50; 650